Textbook biology grade 10th - Malik mohsin jawed (Islamabad National book foundation, 2025)
This supplementary material focuses on developing practical skills in biology for Grade 9 and 10 students. It teaches students how to plan, conduct, and analyze biological experiments safely and accurately. Key areas include using laboratory equipment properly (like microscopes, test tubes, slides), making careful observations, recording data, analyzing results, and drawing valid conclusions. It also emphasizes scientific methods, hypothesis testing, measurement techniques, and error handling. The goal is to make students more confident and skilled in performing experiments and understanding biology through hands-on learning.